STEAM SYSTEM OPTIMIZATION AT A PALM OIL REFINERY PLANT IN SOUTHERN PENINSULAR MALAYSIA - MUHAMMAD SHAHID, MANSOR (Universiti Malaysia Sarawak (UNIMAS), 2020)
System optimization is the method to identify the amount of saving achievable to ensure the equipment used throughout the mill is operated in an optimum condition. Steam system optimization (SSO) in this study is being conducted at the IOI Pan-Century Oleochemical Sdn. Bhd. Pasir Gudang, Johor. The problem being addressed in this study is low temperature of feedwater boiler which in the range of 55℃ to 70℃. This problem probably because of an inefficient configuration of the mill’s steam system and the boiler efficiency only 69.7%. Therefore, the objectives of this research are the current condition of the mill needs to be scrutinized in order to modify the system back to its initial best efficiency, investigate the energy baseline, its productions output, identifying various losses and its cost impact to the mill. On-site measurement has been carried out in order to evaluate the steam system at the mill and do the qualitative analysis. The measurement consists of office data collection, heat losses measurement and stack gas measurement. The energy baseline and the productions output within three years obtained from the office data collection from 2017 to 2019. The software used to evaluate the results of the measurement is 3E Plus: Insulation Program Software and the Steam System Assessment Tool (SSAT). The approximate model of the real steam system has been generated using SSAT. The estimation of total heat losses through the insulation evaluation is around 3.11kW and the cost that being wasted are around MYR 25 152.50 per annually. Through the evaluation of the current operating steam system, the percentage of blowdown losses and the stack losses are 5.8% and 23.4% respectively. The proposed SSO opportunities are installing automatic blowdown control system to reduce the blowdown rate to 2.5% and implement solar thermal application to increase the feedwater temperature. By increase, the efficiency to 80% will improve the steam quality and production output of the mill. The implication of findings is the estimated annual electrical demand saving for the mill is around 2,335 kW and also can save energy demand around 31,826 GJ/yr. Thus, all the objectives are achieved, and the estimated annual net cost savings are MYR 1,305,000.00 through this system optimization.